Level of Preparedness in Pursuing Accountancy Program of Grade 12 ABM Students at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In today's time, when there are so many trials, one should be prepared for them. This is alsothe reason why many people, especially young people and students, give up even though theyhave never tried to do it. Because of the lack of self-confidence and not being prepared for thecourses or paths to be taken, everything usually goes to nothing.Based on the results and interpretations of data in the study, some students can overcome thetrials that come in their lives as much as they can, and others will find other ways to overcomeall of the trials. Based on the results presented, the following recommendations are forwarded:students should make sure they enjoy studying, computing, and presenting with numbersbecause it has a significant impact on how well-prepared they are for the Accountancyprogram.As a student, it is appropriate to develop these skills further by taking the accountancyprogram course so that it is easy to overcome every challenge that comes up in life. Studentsshould practice more analytical skills by playing Sudoku, puzzles, chess, or crosswords sothat their minds develop even deeper decision-making that can be used in real life. Studentswho intend to enroll in the Accountancy program in the upcoming academic year must firstlearn the accounting subject in order to ensure that they are sufficiently prepared to studyaccounting.
Keywords: Education